Peningkatan Permohonan Dispensasi Perkawinan (Dini) di Pengadilan Agama Akibat dari Perubahan Sosial - Safira, Amanda Aurelia; Pratiwi, Amalia Mega; Melan, Melan; Saputra, Stanislaus Michel (Jurnal Pendidikan Islam, 2024)
Marriage is a sacred bond that unites two individuals with the support of society and religious organizations. However, in the ever-changing social dynamics, the phenomenon of early child marriage has become a big problem in Indonesia. This article examines the increase in marriage applications in Religious Courts as a result of social changes that conflict with the rights of children and adults. Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage sets the minimum age limit for marriage. This change has a significant impact on children's basic rights as well as their physical and psychological development. The author also examines the impact of implementing the revised minimum age for marriage policy in 2019 on the rate of child marriage in Indonesia. The research method we use is a normative legal approach in terms of methodology. By considering these issues, this research provides an in-depth understanding of the challenges facing the marriage system in Indonesia as well as the social and regulatory changes that may impact efforts to overcome these challenges.